COVID-19 Crisis: Exploring Community of Inquiry in Online Learning for Sub-Degree Students - Lau, Yui-yip; Tang, Yuk Ming; Chau, Ka Yin; Vyas, Lina; Sandoval-Hernandez, Andres; Wong, Simon (Frontiers in Psychology, 2021)
The COVID-19 pandemic has brought a tremendous impact on pedagogy and students’ learning experience in Hong Kong’s sub-degree education sector. Online learning has become the “sole” solution to deal with student learning challenges during this chaotic period. In this study, we explore online learning for sub-degree students by using Community of Inquiry (CoI). As such, confirmatory factor analysis was conducted on survey data gathered from 287 sub-degree students from the business and engineering disciplines. Results indicated that network speed for online education determines the students’ perceived cognitive presence, social presence, and teaching presence, whereas students’ gender and academic disciplines are not a moderating factor that creates a significant difference in their perceived cognitive presence, social presence, and teaching presence. Our study findings for creating and sustaining a purposeful online learning community are highlighted.